The analysis of training needs in public institutions operating in health care sector in the Podkarpacie Province - Tomasz Skica; Jacek Rodzinka (e-Finanse: Financial Internet Quarterly, 2012)
The article is an attempt at diagnosing training needs of the employees of units operating in health care sector in the Podkarpacie Province. In times of permanent changes affecting each sphere of economy, providers of health care services cannot afford to remain outside this trend. Improving qualifications, adaptability of the offer, influencing its quality, and above all, the awareness of the necessity of these changes, have become an element which is fully integrated also with this sphere of public sector operations. Taking into account the above, the article verifies not only training needs articulated by employees of Health Care Centers (HCC) operating in the Podkarpacie Province, but also the way they are perceived by the managers of these centers, the ability to define training needs and their compatibility with characteristic features of analyzed HCCs. Therefore special emphasis has been placed on demonstrating the variety of diagnosed training needs with reference to such criteria as the size of analyzed centers, the market serviced by them, and their location. These determinants allowed us to conduct a complex analysis of conditions and structure of voiced need for subject training, and as a consequence, contributed to diagnosing the expectations of the health care sector concerning initiatives improving the quality of public services in the health care services area.
Keywords: D60; H51; I11; I12; I19; L30; 330; health care; health care system; health care center (HCC); training needs; medical services market; demand for health care; providers of health-related services; health care economics